School quality and labor market earnings: Some new results on an old debate - Gumilang Aryo Sahadewo (Journal of Applied Economics, 2023)
This study addresses an open debate in the literature about the direct effects of measures of school quality on workers' earnings in the labor market. Card and Kureges (1996) argue that the young sample that Betts (1995) uses understates the effects of the measures of school quality on earnings. The main objective of this study is to investigate the effects of the measures of school quality on earnings at older age, using a recent version of the 1979 National Longitudinal Survey of Youth. The replication of Betts' analysis show that the measures of school quality did not affect earnings when workers were young. However, the estimation shows that the percentage of teachers with a graduate degree significantly affects workers' prime-age earnings. The findings support Card and Krueger's claim that the measures of school quality affected workers' earnings at older age. More importantly, the results reconcile different findings from two strands of studies in the literature using state-level and individual-level data.
Keywords: 330; earnings; Mincer equation; NLSY79; School quality